Carbon Dioxide Utilization and Removal: Building Circular Carbon Economy - Belay Sitotaw Goshu; Muhammad Ridwan (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2026)
Ethiopia, vulnerable to climate extremes like droughts affecting 20 million annually, faces a 68% emissions rise by 2030 without intervention, per NDC 3.0. Carbon dioxide removal (CDR) and utilization (CCU) technologies offer pathways to net-zero by 2050, yet deployment lags due to technological immaturity, barriers, and socioeconomic inequities in a 120 million population reliant on agriculture (70% of the workforce). This study evaluates CDR/CCU viability, barriers, employment transitions, SDG synergies, and policy-financing needs to inform equitable scaling, targeting 50 MtCO₂e annual removal and 1.2 million green jobs by 2030. Methods: Multidimensional assessment integrated raw data (TRL, scalability, negativity, and costs) via bubble charts, barrier heatmaps, lifecycle balances, scalability matrices, employment projections, SDG linkages, regional vulnerabilities, policy timelines, complexity priorities, and financing mixes. Quantitative modeling employed correlations (e.g., r = 0.62 for scalability-negativity), econometric simulations, and geospatial analysis across 10 technologies and 9 regions. Findings: CDR outperforms in negativity (0.82 mean) and permanence (3,060 years) but trails CCU economically (-27.5 USD/tCO₂); barriers peak economically (8.3 severity) with $1.92B financing gaps; transitions yield 2.5 million jobs and a 20.6-point SDG uplift (strongest SDG 7 linkage, 10/10); Oromia anchors potential (5.8 growth); policies favor regulatory (5 instruments), and complexity prioritizes renewables (120k jobs, Figure 12); $3.5B is mobilized via 35% international finance. Novelty: First integrated Ethiopia-centric framework blending technoeconomic, barrier, just transition, and policy analyses, revealing 70:30 CDR-CCU portfolios for 10 GtCO₂/year at 80 USD/t aggregate, with regional equity modeling reducing vuln-poverty correlations by 25%. Viable for resilient net-zero, amplifying co-benefits amid 1.5°C risks. Allocate $1B phased investments (40% renewables/forestry), harmonize regulations, and reskill 500k workers for inclusion.